2017
DOI: 10.1080/01616412.2017.1390933
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional alterations of the heart in Parkinson’s disease

Abstract: PD is significantly associated with increased concentric left ventricular hypertrophy and diastolic dysfunction. Advanced stages of PD are associated with a more severe cardiac affection. These findings can explain the increase of heart failure in PD patients. Cardiomyopathy could be a non-motor parkinsonian symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…PD patients die from different causes including aspiration pneumonia, dementia, old age, cancer, cardiovascular disease and sudden unexpected death 2123 . Several studies have shown that changes in cardiac function may be present in PD patients 12,24 . Scorza et al .…”
Section: Discussionmentioning
confidence: 99%
“…PD patients die from different causes including aspiration pneumonia, dementia, old age, cancer, cardiovascular disease and sudden unexpected death 2123 . Several studies have shown that changes in cardiac function may be present in PD patients 12,24 . Scorza et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac dysautonomia and sympathetic nervous system impairments of the heart have been reported in neurodegenerative diseases (Goldstein 2014, Joers & Emborg 2014, Piqueras-Flores et al 2017. MPTP toxicity studies in mice have suggested a selective vulnerability of monoamine cells.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of heart failure has been found to be twice as high among PD patients compared with overall population regardless of any other heart or cardiovascular disease risk factors [65]. PD is significantly associated with increased concentric left ventricular hypertrophy and diastolic dysfunction, and advanced stages of PD are associated with a more severe cardiac affection [66], which may explain the higher prevalence of heart failure in PD patients. As a mouse model of PD, PINK1 KO mice also showed left ventricular dysfunction and cardiac hypertrophy [67].…”
Section: Discussionmentioning
confidence: 99%